Systems Analysis of the Response of Photosynthesis, Metabolism, and Growth to an Increase in Irradiance in the Photosynthetic Model Organism Chlamydomonas reinhardtii . Issue 6 (3rd June 2014) - Mettler, Tabea; Mühlhaus, Timo; Hemme, Dorothea; Schöttler, Mark-Aurel; Rupprecht, Jens; Idoine, Adam; Veyel, Daniel; Pal, Sunil Kumar; Yaneva-Roder, Liliya; Winck, Flavia Vischi; Sommer, Frederik; Vosloh, Daniel; et al.
Abstract : Systems analysis reveals that Chlamydomonas reinhardtii responds flexibly to an increase in light intensity. Rising metabolite levels and posttranslation regulation facilitate a rapid increase in the rate of carbon fixation and a slightly delayed increase in the rate of growth, while slower changes in protein abundance adjust allocation and relieve potential bottlenecks under the new conditions. Abstract: We investigated the systems response of metabolism and growth after an increase in irradiance in the nonsaturating range in the algal model Chlamydomonas reinhardtii . In a three-step process, photosynthesis and the levels of metabolites increased immediately, growth increased after 10 to 15 min, and transcript and protein abundance responded by 40 and 120 to 240 min, respectively. In the first phase, starch and metabolites provided a transient buffer for carbon until growth increased. This uncouples photosynthesis from growth in a fluctuating light environment. In the first and second phases, rising metabolite levels and increased polysome loading drove an increase in fluxes. Most Calvin-Benson cycle (CBC ) enzymes were substrate-limited in vivo, and strikingly, many were present at higher concentrations than their substrates, explaining how rising metabolite levels stimulate CBC flux. Rubisco, fructose-1, 6-biosphosphatase, and seduheptulose-1, 7-bisphosphatase were close to substrate saturation in vivo, and flux was increased by posttranslational activation. In the third phase, changes in abundance of particular proteins, including increases in plastidial ATP synthase and some CBC enzymes, relieved potential bottlenecks and readjusted protein allocation between different processes. Despite reasonable overall agreement between changes in transcript and protein abundance ( R 2 = 0.24), many proteins, including those in photosynthesis, changed independently of transcript abundance.